2022
DOI: 10.1186/s13045-022-01333-0
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic and bleeding complications in patients with chronic lymphocytic leukemia and severe COVID-19: a study of ERIC, the European Research Initiative on CLL

Abstract: Background Patients with chronic lymphocytic leukemia (CLL) may be more susceptible to COVID-19 related poor outcomes, including thrombosis and death, due to the advanced age, the presence of comorbidities, and the disease and treatment-related immune deficiency. The aim of this study was to assess the risk of thrombosis and bleeding in patients with CLL affected by severe COVID-19. Methods This is a retrospective multicenter study conducted by ERI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Patients with hematological malignancies who develop coronavirus infectious dis-ease (COVID-19) following infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) usually display an increased risk of hospitalization and intensive care unit (ICU) admission, with an estimated risk of death up to 34% (1)(2)(3)(4). This is likely due to the severe impairment of these patients' immune systems, weakened by the hematological diseases themselves as well as their treatments, which results in ineffective cellular (5)(6)(7) and humoral (8)(9)(10) responses to SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with hematological malignancies who develop coronavirus infectious dis-ease (COVID-19) following infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) usually display an increased risk of hospitalization and intensive care unit (ICU) admission, with an estimated risk of death up to 34% (1)(2)(3)(4). This is likely due to the severe impairment of these patients' immune systems, weakened by the hematological diseases themselves as well as their treatments, which results in ineffective cellular (5)(6)(7) and humoral (8)(9)(10) responses to SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key concerns for patients with hematological malignancies during the COVID-19 pandemic is the increased vulnerability to severe illness. The weakened immune response can make it difficult for these patients to fight the infection, including the respiratory complications associated with COVID-19, resulting in high rate of hospitalization, intensive care unit admission and death (1)(2)(3). Several studies also suggest that COVID-19 can exacerbate the complications of hematological malignancies, leading to disruptions in treatment schedules and heightened concerns about disease management.…”
Section: Covid-19 Therapies In Patients With Hematologic Malignanciesmentioning
confidence: 99%
“…Swiftly conducted real‐world studies by ERIC and others during the COVID‐19 pandemic exemplify this potential, providing useful information on the outcomes of patients with CLL infected with SARS‐COV‐2 and their responses to COVID‐19 vaccines. 115 , 116 , 117 , 118 , 119 , 120 , 121 Last but not least, RWD has also been used in more elaborate approaches involving artificial intelligence (AI). Indicatively, Agius et al have reported a machine‐learning approach for identifying patients with a high risk of infection, underlining the myriad possibilities of utilizing RWD toward the realization of PM.…”
Section: Rwd Aggregationmentioning
confidence: 99%